Epistemologi Fadhilah Doa Kepada Orang Meninggal: Analisis Perspektif NU dan Muhammadiyah - Imaduddin (Farabi, 2020)
This article will examine the nature of prayer specifically for the dead. As in QS. Muhammad verse 19 and in the Sahih Muslim book; 3084 recommends to always draw closer to Allah, including by praying. Fadhilah until the reward was a controversial topic between NU and Muhammadiyah as the two largest ORMAS in Indonesia. So it is necessary to have a substantive study of the philosophy of prayer by examining the arguments for the reward of prayer to the dead. Nahdliyyin said praying for people to die in merit until they were prayed for. On the contrary, the Muhammadiyah group rejected the argument, they said that praying for the dead would not benefit those who were prayed for and that would be futile. This research with library research approach shows that there is a very contrast between the two ORMAS. The controversy in the meaning of prayer to the dead is one of the khilafiyah, because each cleric has an opinion based on a strong argument, so that the Muslim community in Indonesia does not need to be ambiguous in taking action, regarding the arrival of the prayer for the dead